A educação de jovens e adultos (EJA) segundo a pedagogia de Paulo Freire - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The article is based on the results and postulates enunciated in the book "Education as a practice of freedom", which synthesizes the historical and cultural reasons that grounded its scientific orientation in the development of the methods satisfactory for Adult Literacy. The objective of the article was to analyze the Education of Young and Adults (EJA) according to the pedagogy of Paulo Freire. The methodology employed consisted of the dialectical historical method that critically analyzes the researched object, adopting the premise that there are multiple historical, social and political determinations in adult education. The research was qualitative, based on the analysis of books and scientific articles, selected and interpreted according to the intrinsic orientations of bibliographic research. The results presented studies about the transition process experienced by Brazilian society and, in their historical social process in the 1960s and 1970s, described the impediments caused to the people in what concerns the right to democracy; offered descriptions of the processes of education versus massification; and understood the education of the masses (adults) through awareness. It was concluded that pedagogical work with youth and adults needs to preserve the knowledge of the world that this man has, the way he understands and interacts with the characteristics of reality, life and his daily life, bringing them to be debated in the classroom . From these practices, one can establish the construction of contents capable of fostering the learning of written language, the understanding of what characterizes a representation and the symbolic activity for the education of young people and adults. In this perspective, all learning is a dynamic work in which the learner is always moving, building and rebuilding his personal and group universe, exerting an act of understanding the world.
Keywords: Educação de jovens e adultos; Estratégias pedagógicas; Alfabetização de adultos